Enhancing Global Poliomyelitis Surveillance Performance is Crucial for Eradication Efforts: Meningkatkan Kinerja Surveilans Polio Global Sangat Penting untuk Upaya Pemberantasan - Arkan Hashim Ibrahim; Mazin Khalid Abdullah; Marwah Q. Salman (Universitas Muhammadiyah Sidoarjo, 2024)
Background: Poliomyelitis remains a significant public health challenge, with global efforts focused on its eradication. One critical strategy in this endeavor is the implementation of an acute flaccid paralysis (AFP) surveillance system, which is essential for early detection and response to poliovirus transmission. Specific Background: Despite the system's importance, there is limited evaluation of its performance, particularly in regions like Diyala province, Iraq. Knowledge Gap: Previous studies have not adequately assessed the AFP surveillance performance indicators specific to this region, necessitating a comprehensive analysis. Aims: This study aimed to evaluate the performance indicators of the AFP surveillance system in Diyala province during 2021, utilizing established World Health Organization (WHO) standards. Results: The cross-sectional study analyzed data from seven primary health care centers. Key findings revealed a Non-Polio Acute Flaccid Paralysis rate of 5.11 per 100,000 children under 15 years. Performance indicators included 100% reporting completeness, 95% timeliness of notification and investigation, and 97% stool quality for laboratory analysis. Furthermore, 97.3% of specimens reached the national laboratory within three days, demonstrating high operational efficiency. Novelty: This study is one of the first to provide a detailed evaluation of the AFP surveillance system in Diyala province, highlighting areas of strength and compliance with WHO targets. Implications: The findings underscore the effectiveness of the AFP surveillance system in this region, suggesting that its continued implementation can significantly contribute to the global eradication efforts of poliomyelitis while also serving as a model for similar evaluations in other regions. Highlights: High reporting completeness and timeliness in AFP surveillance. Non-Polio AFP rate exceeds WHO targets, indicating effective monitoring. Study supports global efforts toward poliomyelitis eradication. Keywords: Poliomyelitis, Acute Flaccid Paralysis, Surveillance System, Performance Indicators, Iraq